Enrichment of the embryonic stem cell reprogramming factors Oct4, Nanog, Myc, and Sox2 in benign and malignant vascular tumors. Issue 1 (December 2015) - Amaya, Clarissa; Bryan, Brad
Abstract Background The "stem cell theory of cancer" states that a subpopulation of cells with stem cell-like properties plays a central role in the formation, sustainment, spread, and drug resistant characteristics of malignant tumors. Recent studies have isolated distinct cell populations from infantile hemangiomas that display properties equivalent to aberrant progenitor cells, suggesting that, in addition to malignant tumors, benign tumors may also contain a stem cell-like component. Methods In this study, the expression levels of the embryonic stem cell reprogramming factors Oct4, Nanog, Myc, Sox2, and Klf4 were examined via immunohistochemistry in a panel of 71 benign, borderline, and malignant vascular tumors including capillary hemangioma, cavernous hemangioma, granulomatous hemangioma, venous hemangioma, hemangioendothelioma, hemangiopericytoma, and angiosarcoma. Antigenicity for each protein was quantified based on staining intensity and percentage of tissue positive for each antigen, and subsequently compared to data obtained from two control tissue sets: 10 vascular tissues and a panel of 58 various malignant sarcomas. Results and discussion With the exception of Myc (which was only present in a subset of benign, borderline, and malignant tumors), Oct4, Nanog, Sox2, and Klf4 were detectable at variable levels across both normal and diseased tissues. Semi-quantitative evaluation of our immunohistochemical staining revealed that protein expression of Oct4, Nanog, Myc, and Sox2, but not Klf4, was significantly increased in benign, borderline, and malignant vascular tumors relative to non-diseased vascular tissue controls. Interestingly, the enhanced levels of Oct4, Nanog, Myc, and Sox2 protein were approximately equivalent between benign, borderline, and malignant vascular tumors. Conclusions These findings provide supporting evidence that enrichment for proteins involved in pluripotency is not restricted solely to malignant tumors as is suggested by the "stem cell theory of cancer", but additionally extends to common benign vascular tumors such as hemangiomas.